Sistem Informasi Manajemen Aset pada Amik Akmi Baturaja - Salamudin, Salamudin; Meilantika, Dian Meilantika (SISKOMTI: Jurnal Sistem Informasi Komputer dan Teknologi Informasi, 2019)
Management of assets in a company is very important thing to do. Management of goods assets in AMIK "AKMI" Baturaja has been carried out with Microsoft Excel applications in the format of inventory items. In this application has limitations such as manual entry, there is no history of data changes made or log data, no notifications, difficult to use simultaneously, data accuracy is doubtful, data matching or recording takes a long time, and is not user-friendly . This study aims to analyze and design the system of management of all assets in AKMI Baturaja. Through analysis and design of this system the author intends to provide suggestions for institutions to implement the Asset Information System. This information system has been successfully designed and provides asset information management functionality which includes asset registration, asset placement, asset transfer, maintenance records, asset deletion, asset tracking, and report generation. Designing of a web-based asset information system is done by using an object-oriented approach.